Integrated spatial technology framework for greenhouse gas mitigation in grain production in Western Australia - Engelbrecht, Deborah (Curtin University, 2015)
The research focused on integrating life cycle assessment, remote sensing and geographical information systems to develop an integrated spatial technology framework. The framework was developed specifically to identify mitigation strategies based on cleaner production methods for the grain industry in south-western Australia, with varying agro-ecological zones, climatic conditions and farm management practices. During validation of the integrated spatial technology framework the use of fertilisers was generally identified as the source of most of the hotspots.